Experimental Study Of A Nonlinear Circuit Described By Duffing's Equation - Volos, Christos K.; Kyprianidis, Ioannis M.; Stouboulos, Ioannis N. (İstanbul Kültür Üniversitesi Yayınları, 2006)
We have studied experimentallyan electronic circuit that implements the Duffing equation. The circuit appears periodic and non-periodic (chaotic) dynamics behavior, as we vary the amplitude of the driving voltage signal Va. The expected operation of the circuit was confirmed, by comparing the experimental results with the results of the simulation. From the study of the circuit's behavior, very important phenomena conceming the Chaos theory were detected, such as the great sensitivity of the circuit to initial conditions, the route to chaos through the mechanism of period doubling and the phenomenon of crisis of chaotic attractors.
Keywords: chaos; Duffing equation; phase portrait; poincare map; bifurcation diagram; period doubling; crisis of attractor; kaos; Duffing denklemi; faz portresi; poincare haritası; çatallanma diyagramı; iki kat dönemi; çekerin krizi